Evidence adaptation and tailored implementation of family bereavement support in specialised palliative care: A multi-method study - Myrta Kohler; Qëndresa Thaqi; Silke Kuske; Torsten Schwalbach; Marco Riguzzi; Rahel Naef (International Journal of Nursing Studies Advances)
Background: Families experiencing the loss of their close other following advanced illness have varying degrees of needs that stretch into bereavement. Evidence-based recommendations for bereavement support are often not well implemented in palliative care services due to multiple system barriers and lack of contextual fit. To close this know-do gap, we undertook an implementation science research project. Objective: To adapt evidence-informed recommendations for supporting bereaved families to the local context, and to develop a tailored implementation strategy for their integration in specialised palliative care services. Settings and participants: Two specialised palliative care services located at urban teaching hospitals in German-speaking Switzerland. Participants were palliative care staff working in the service, including nurses, physicians, chaplains, psychologists, and two service users. Methods: Multi-method implementation research project combining community engagement strategies, qualitative contextual analysis, and theory-driven implementation design processes for integrating evidence-informed interventions in new contexts: First, evidence was identified and adapted through co-design staff workshops and service user consultations, following intervention adaptation guidelines. Next, focus group interviews were held to identify barriers and facilitators to implementation, informed by the Consolidated Framework for Implementation Research and analysed using qualitative content analysis. Drawing on implementation mapping methodology, a systematic and participatory process was used to develop an implementation plan that specified activities needed to address identified barriers and support integration into palliative care services. Results: The study resulted in an adapted bereavement support pathway with three core functions of evidence-informed practices delivered during dying, at death, three-to-six, and if necessary nine-to-twelve months post-loss: screening and assessing family needs and risks, intervention and support activities for families, and team collaboration and coordination within and across providers. Implementation was expected to be influenced by the features of the intervention itself, staff competencies, and organisational conditions, with resources required being a frequent barrier, whereas workplace culture and the project-related network acted as facilitators. A multifaceted implementation strategy with 16 distinct activities was developed to reach 70 % of bereaved families: designing a practical, implementable pathway, creating necessary team capacity and roles, optimizing workflow, offering education and clinician support, ensuring leadership and organisational commitment, and facilitating mutual exchange and learning. An implementation research logic model specified expected mechanisms of impact and outcomes. Conclusions: The project resulted in an adapted bereavement support intervention fitted to local palliative care contexts and a tailored implementation plan. Adapting evidence to specific contexts and understanding potential barriers and facilitators is necessary to prepare implementation. Registration: https://osf.io/qgr7y